COMPARATIVE ANALYSIS OF PSYCHOMETRIC TESTING ON TWO PROFESSIONALS TO SELECT BEST CANDIDATE DURING SELECTION PROCESS - Naik, Shruti D; Madan, Sahana; Sharma, Shobhraj (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this paper was to measure individuals’ mental capabilities and preferred behavioral style fitting the suitability for a role with training team. The position was of a training manager which required aptitude and cognitive abilities. The tests were used to identify the extent to which candidates’ match skills, knowledge, motives and abilities required to perform the role. Various tests were administered on both the candidates. An ability test was also designed and administered on the top performers of the organization. All the information were collected from the psychometric (PSI), Career Drivers (RSI), Motives (TAT) and ability tests to identify the hidden aspects of candidates followed by a presentation and face-to-face interview.